2013
DOI: 10.1142/s0219649213500354
|View full text |Cite
|
Sign up to set email alerts
|

Twitter Content Categorisation: A Public Library Perspective

Abstract: With the rise of social media, many library and information services have begun to incorporate a wide variety of social media and social networking applications into their systems and services. Among the mainstream social networking applications, micro-blogging, in general, and Twitter, in particular, have gained increasing popularity. This paper reports the results of an exploratory study of the application of Twitter in the context of a large public library system. Specifically, this study has sampled, conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 12 publications
2
50
1
1
Order By: Relevance
“…Early research on libraries and Twitter largely focused on how libraries were using Twitter, whether through case studies examining how an individual library implemented its Twitter strategy (Cahill, 2011) or examinations of library tweets (Aharony, 2010;Shiri & Rathi, 2013). Aharony (2010) found that public library tweets fell into four categories: "Library in general," "information about," "general recommendations," and "technology."…”
Section: Microblogging As Information Sharing and Community Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Early research on libraries and Twitter largely focused on how libraries were using Twitter, whether through case studies examining how an individual library implemented its Twitter strategy (Cahill, 2011) or examinations of library tweets (Aharony, 2010;Shiri & Rathi, 2013). Aharony (2010) found that public library tweets fell into four categories: "Library in general," "information about," "general recommendations," and "technology."…”
Section: Microblogging As Information Sharing and Community Engagementmentioning
confidence: 99%
“…Aharony (2010) found that public library tweets fell into four categories: "Library in general," "information about," "general recommendations," and "technology." Shiri and Rathi (2013) expanded on Aharony's (2010) categorization scheme. Like Aharony (2010), Shiri and Rathi (2013) found public libraries tweeted to communicate traditional library interests, share information, and make recommendations; however, they also found that interactions with users, such as responding to twitter users about library-related services (advisory services) and discussions with users about films and other kinds of popular culture (informal conversation) were amongst the top five categories of tweets.…”
Section: Microblogging As Information Sharing and Community Engagementmentioning
confidence: 99%
“…and that it led to a lesser engagement and a low audience participation. As mentioned in [7], tweet analysis has led to a large number of studies in many do-mains such as ideology prediction in Information Sciences [4], natural disaster anticipation in Emergency [15] and tracking epidemic [13] while work in Social Sciences and Digital Humanities has developed tweet classifications [16]. However, few studies aim at classifying tweets according to communication classes.…”
Section: Related Workmentioning
confidence: 99%
“…Del Bosque and colleagues (2012) found similar results in their 2012 study of academic library Twitter use, with the primary focus of tweets relating to library resources and promoting library events. Likewise, Shiri and Rathi's (2013) content analysis of tweets from the Edmonton Public Library (EPL) indicated that the library used Twitter primarily to communicate library-related announcements such as hours of operation, to share information about "books, movies and other media", and to provide recommendations "designed to lead the reader to the EPL catalogue". More recently, Young and Rossman (2015) reported a shift in Montana State University Library's tweeting behaviour away from tweets consistent with the Salesperson persona towards tweets that are more consistent with the Curator.…”
Section: Literature Reviewmentioning
confidence: 99%